Resettling and reshaping social ecology: Social stratification and exploitation practices in Mahaweli resettlement area in Sri Lanka - Epa, Pulsie; Gunasekara, Suranjith (SIMULACRA: JURNAL SOSIOLOGI, 2024)
The Sri Lankan government places a high priority on rural development, as a majority of the population living below the poverty line resides in rural areas. Progress is hindered by limited accessibility and resources. Resettlement was used as a strategy to improve the living conditions of the people. New resettlement practices have brought about significant changes in communities, shifting from traditional to modern social systems. This study investigates the emergence of social stratification and their role in facilitating exploitation practices in the Mahaweli resettlement scheme, utilizing sociological theory to understand stratification and inequalities. The study focuses on the social stratification and exploitation patterns in resettlement areas, using a literature review and qualitative data analysis to explore the mode of production, synthesis of social stratification, examination of exploitation among different social strata, and rationalization of exploitation within these areas. External interventions have led to the establishment of social stratification in the resettlement areas, but the strict state administrative framework has posed challenges in maintaining autonomy and establishing a self-reliant social and economic system. Consequently, poverty levels in these regions have increased due to the emergence of new social hierarchies and exploitation in various ways underscoring the need for more comprehensive and effective resettlement initiatives.